Os mapas do Roteiro Turístico e Económico de Portugal (ROTEP) e a promoção municipal em representações cartográficas do Estado Novo - Martins, Luís Paulo Saldanha (2020)
Within the scope of the Touristic and Economic Roadmap of Portugal, between 1945 and 1977, 194 publications were produced, 136 of which refer to representations of municipalities in Mainland Portugal. The publisher aimed to achieve a wide coverage of the national territory, having as main objectives, as explained in the name, tourist promotion and economic information about the municipalities represented. It also assumed a very evident cultural dimension, identifiable in the symbolic elements present in the documents produced, both associated with the material and immaterial heritage of the municipality.Scientific knowledge, politics and culture intersect in the organization of ROTEP scripts. With the sponsorship of Amorim Girão that frames the production of the scripts, the scientific framework is evident, while the political tutelage is manifested through the support, in some of the numbers, of the Ministry of National Education and the National Secretariat for Information and Tourism. The cultural dimension, on the other hand, comes with the valorization of traditional elements, exalted in so many of the dimensions included in the representations, constituting identity marks of these publications, unequivocally identifiable in the organization of most of the consulted documents.Thus, the documents produced by ROTEP, the vast majority with the organization of photographer Camacho Pereira, contributed to expand the knowledge of municipalities and regions, to accompany the transformations that occurred in the forties of the 20th century and to emphasize the elements of territorial differentiation, allowing simultaneously deepen the debate on the themes of tourism and cartography, in force during the Estado Novo, having as a first argument one of the motives of the publication: "With ROTEP the Tourist knows what has to do in the place he visits...".